2018
DOI: 10.1530/eje-18-0083
|View full text |Cite
|
Sign up to set email alerts
|

Differences between ATA, AACE/ACE/AME and ACR TI-RADS ultrasound classifications performance in identifying cytological high-risk thyroid nodules

Abstract: The ACR TI-RADS classification system has the highest area under the ROC curve for the identification of cytological high-risk nodules. ATA classification leaves 'unclassified' nodules at relatively high risk of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 34 publications
4
66
3
2
Order By: Relevance
“…). It is recognized that ATA has limitations in classifying isoechoic and hyperechoic nodules with malignant features, as well as the relevant number of malignancies in this group of nodules . Given the high frequency of these findings among FTC, future guidelines should incorporate these results.…”
Section: Discussionmentioning
confidence: 99%
“…). It is recognized that ATA has limitations in classifying isoechoic and hyperechoic nodules with malignant features, as well as the relevant number of malignancies in this group of nodules . Given the high frequency of these findings among FTC, future guidelines should incorporate these results.…”
Section: Discussionmentioning
confidence: 99%
“…Originalkohorte mit 3650 Knoten [29] TI-RADS nach Park [27] Muster + Punktesumme [32], [33], [34], [35], [37], [39], [40] AACE / ACE / AME 2016 [30] Muster-basiert [48]. Eine glatte oder lediglich unscharfe Begrenzung zwischen solidem und zystischem Anteil weist auf BenignitĂ€t hin, eine mikrolobulierte Begrenzung auf MalignitĂ€t, v. a. in Kombination mit Mikrokalzifikationen des soliden Anteils [49], [50].…”
Section: Alleunclassified
“…DignitĂ€tsbeurteilung: Taller-than-wide ist zwar ein wenig sensitives, aber hochspezifisches und hochsuspektes Kriterium [56], [57]. [33], [35], [37], [65].…”
Section: Alleunclassified
“…Ultrasound is a widely accepted diagnostic method for examining thyroid [23][24][25][26][27], but several studies have reported that it is less useful in differentiating between PTL and HT [28]. Ultrasound suffers the limitations of being non-specific [29][30][31]. CT has been introduced to an augment technique of diagnosis of thyroid disease [32].…”
Section: Discussionmentioning
confidence: 99%